L’économie québécoise face à la concurrence extérieure : les fondements scientifiques de la politique d’achat préférentiel du Québec - Bernier, Ivan (Études internationales, 1984)
The literature on the decision-making process s of governments in the field of trade has developped in recent years a number of models that stress different aspects of the subject. One aspect, however, that has rarely been examined closely is the exact role played by studies in this decision-making process. How serious are they, scientifically speaking? How are they considered by governments? What is their impacts? Such questions remain largely unanswered. In this paper, an effort is made to shed some light on this aspect of the decision-making process, the chosen field of enquiry being the Quebec Government's procurement policy. After considering various studies directly related to the implementation of this policy, the conclusion is reached that in general they were not very thorough and had a rather limited role in the final decision to implement the policy. More fundamentally, one is left with the impression that scientific research, as a tool for reaching decision in the field of international trade, is seen by governments with some degree of suspicion.